Revisiting El Niño Modokis - Marathe, Shamal; Ashok, Karumuri; Swapna, P.; Sabin, T. P. (Climate dynamics, 2015)
The suggestion that there exist two types of El Niño in the tropical Pacific has generated a debate in the community. Applying various linear and non-linear approaches and composite analysis technique on observed and reanalyzed climate datasets primarily for the 1950–2010 period, we revisit the variability of the tropical Pacific in the light of this debate. Our objective is to examine whether the proposed El Niño Modokis need a classification distinct from canonical El Niños. Even if the distinction is subject to short data records, we demonstrate that the El Niño Modoki events indeed display a seasonal evolution and teleconnections different from the canonical El Niños, and that the distinction is not subject to inclusion of the two extreme El Niños 1982 and 1997 as canonical El Niños. We show that the El Niño Modoki events are not an artifact associated with the orthogonality constraint associated with the EOF technique. Our cluster analysis shows that evolutions of the canonical El Niño and El Niño Modokis through various seasons differ from one another. Importantly, the dynamic and thermodynamic air–sea coupling strength is distinctly different between the El Niño Modoki and the canonical El Niño events. We find that, dynamic feedback intensity is stronger for El Niño Modoki (canonical El Niño) during boreal summer (winter); though the air–sea coupling strength, a major contributor to Bjerknes feedback, is maximum for Modokis during the developing stages, it decreases thereafter. In case of thermodynamic feedback intensity, SST-wind-evaporation feedback is dominant for El Niños while SST-SHF feedback is important during El Niño Modokis. However, we find that the thermodynamic feedback values significantly differ across the flux datasets.